COLOR POLYMORPHISMS ON COMMON CARP CULTURED IN INDONESIA - Rudhy Gustiano (Zuriat, 2005)
In most cases, phenotypic variation is partly a result of genetic differences and partly environmental in origin. It appears that polymorphism is caused by some gene frequency changes which are due to natural selection. Morphological markers (body color and scale pattern) are the easiest indicators to identify and important when large sample are involved. In addition, the coloration in food fishes is often important in determining market price. Moreover, the production of fish depends not only on their genes and environment but also on the interaction of these two factors. Several investigations reported that some color genes have pleiotropic effect on growth rate and viability of fish. Hence, it is important to understand the basis of color polymorphisms in order toenhance genetic improvement and brood stock management plans for common carp in Indonesia. The occurrence color polymorphism showed that the proportion (%) of  each color morphs in each farm showed a high proportion of green color morph in common carp stocks. Dark colored carps are preferred over brightly pigmented ones. Bright colored morphs are preferred to the colorless (white). Comparison among the red, yellow, white, green and blue color morphs of common carp showed that each morph has its own specific chromatophore type densities, pigment distribution pattern. The study also showed that color variation is governed by the types of pigment cells present. The genetic color polymorphisms study showed that various color phenotypes were mainly controlled by simple Mendelian inheritance. Symbols for gene loci proposed as follow: B1 and B2 for common green body background (wild type allele), R1 and R2 for red and yellow. T is for wild nontransparent scale type and P for uniform body color background. B1 and B2 are epistatic to R1 and R2 genes. On the basis of the growth rate comparison results obtained on common carp in Indonesia, there was evidence that dark color (green and blue) common carp gained weight faster than the light color one (red). Green and blue colored showed similarity in growth performance.